Astronomia na educação infantil: uma revisão bibliográfica em teses e dissertações brasileiras - Pessutto, Andrezza Tiana (2024)
The importance of Astronomy in a child's life and throughout their school career, especially in Early Childhood Education, goes far beyond the development of cognitive, social and emotional aspects. This area of ​​science favors the understanding of the world in which children live, so that they do not fall short of everyday natural phenomena and help them in the elaboration of concepts in the following school stages. However, the presence of Astronomy in the children's educational environment is recent, and there is a need for research that supports work in the classroom, in order to strengthen its practice in Early Childhood Education. In this research, based on previous academic productions, we analyzed the way in which Astronomy has been considered in Early Childhood Education, highlighting its characteristics and direction of studies in the area. The main question of this dissertation was: What does Brazilian research reveal about Astronomy in Early Childhood Education? This is a qualitative study, with bibliographical research, of the state of knowledge type. Using multiple descriptors, without a time frame, 13 works related to the theme, available in the CAPES Theses and Dissertations Bank, were analyzed, including one thesis and 12 dissertations. The analysis considered two categories defined a priori: (i) Contextualization of studies; (ii) Astronomy and its approach to Early Childhood Education. Each category was divided into subcategories. The analysis of the first category revealed that research production is concentrated between the years 2016 and 2023; the year with the highest number of publications was 2019; the Brazilian regions with publications in the area are the north, south and southeast; most studies are in the southeast region, predominantly in São Paulo, at the Universidade Estadual Paulista Júlio de Mesquita Filho; eleven postgraduate programs led the advancement of the theme in Brazil, divided into nine areas of knowledge, the majority linked to the area of ​​Science, associated with Astronomy at BNCC, although its presence can already be observed in specific postgraduate programs in education. It was also observed the origin of four educational products with guidelines for working on the topic in the classroom and that the research is aimed at students over the age of four. In the analysis of the second category, it was found that the majority of research focuses on the area of ​​natural sciences or scientific literacy; the researchers' intention was to understand the development of the teaching-learning process and contribute to the study of specific pedagogical resources for the area; in objectives, the most used verbs, such as analyze, investigate and contribute, reveal the need for investigations to continue to be developed; all research is qualitative in nature; data production took place through participatory research, field study and action research; the most used instruments for data collection were observations, notes and audiovisual records; the most used analysis procedure was content analysis. Among the main results observed, the ones that stand out the most are the favoring of learning that occurred in the research process and the unanimous finding of researchers regarding the proof of learning through Astronomy in Early Childhood Education, as long as there is pedagogical commitment and appropriate scientific basis.